Pokémon. Sword & shield. Volume 4 - Kusaka, Hidenori; Tanzer, Molly (Viz Media, LLC, 2022)
"Casey and Henry's journey through the Galar region continues! Casey is finally reunited with another of her missing Pokémon! Will she be able to find all of them? And can Henry win the challenge against Allister?!"--Provided by publisher.